Design and Build English Spell Application with Image Objects as an Android-Based Early Childhood Learning Media - Andi Hutami Endang; Kamil Malik; Fitria Fitria (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this research is the application of games as educational media, there is no doubt that educational games can support the educational process because educational games are superior in several aspects when compared to conventional learning methods. This English spelling educational game uses object images as an Android-based early childhood learning media. Its superiority lies in its visualization and attractive appearance which aims to train Listen and Spell in English.The method used is the waterfall method which includes 5 stages namely needs analysis, system design, writing program code, testing programs and implementing programs. The result of this educational game will later display four categories of pictorial questions namely Carnivores, Herbivores, Fruits, Transportations and equipped with sound for each picture played by a single player (Single Player).